Porous core-shell wave-absorbing aerogel and preparation method thereof

By preparing porous core-shell-like wave absorbing aerogel, combined with gelatin/hydroxyethylcellulose aerogel and hollow CoFe2O4@ graphene composite, the problems of electromagnetic wave impedance mismatch and high material density are solved, and high-efficiency electromagnetic wave absorption is achieved and magnetic loss increase the absorption bandwidth.

CN119161635APending Publication Date: 2024-12-20SHENZHEN SUNWAY COMM
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410862376.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-28
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The prior art lacks a wave absorbing material that combines the excellent characteristics of graphene, CoFe2O4 and gelatin/hydroxyethyl cellulose aerogel, and it is difficult to effectively solve the problems of electromagnetic wave impedance mismatch and high material density, resulting in poor electromagnetic wave reflection.

Method used

By preparing porous core-shell-like wave absorbing aerogel, the impregnation method of gelatin/hydroxyethylcellulose aerogel and hollow CoFe2O4@ graphene composite material is used, and the porous structure of the aerogel and the electromagnetic wave loss mechanism of the hollow composite material are used. , improve impedance mismatch and reduce electromagnetic wave reflection.

Benefits of technology

It realizes efficient absorption of electromagnetic waves, effectively absorbs frequency bandwidth, reduces electromagnetic wave reflection, and the magnetism of CoFe2O4 enhances the magnetic loss effect of electromagnetic waves.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161635A_ABST
    Figure CN119161635A_ABST
Patent Text Reader

Abstract

The invention provides porous core-shell wave-absorbing aerogel and a preparation method thereof. The preparation method of the porous core-shell wave-absorbing aerogel comprises the following steps: providing or preparing gelatin / hydroxyethyl cellulose aerogel; providing or preparing a dispersion liquid of the hollow CoFe2O4 and graphene composite material; the gelatin / hydroxyethyl cellulose aerogel is soaked in the dispersion liquid; the gelatin / hydroxyethyl cellulose aerogel is taken out of the dispersion liquid and dried, and the porous core-shell wave-absorbing aerogel is obtained. The porous core-shell wave-absorbing aerogel is prepared on the basis of the gelatin / hydroxyethyl cellulose aerogel and by taking the hollow CoFe2O4 and graphene composite material as an electromagnetic wave absorbent through an impregnation method, and the porous structure of the aerogel and the hollow CoFe2O4 and graphene composite material can effectively improve the impedance mismatch phenomenon and reduce the reflection of electromagnetic waves; and the CoFe2O4 has magnetism so as to carry out magnetic loss on electromagnetic waves.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electronic communication technology, and in particular to a porous core-shell absorbing aerogel and a preparation method thereof. Background Art

[0002] The increasing popularity of information technology has caused the generation of environmental electromagnetic electromagnetic wave (EMW) pollution, which has brought various risks to people, equipment utilization and military safety. Although traditional electromagnetic shielding materials have high shielding effectiveness, serious electromagnetic wave secondary pollution makes the electromagnetic environment more complicated. Therefore, it is particularly important to develop high impedance matching EMW absorbers.

[0003] A large number of studies have found that introducing magnetic components into composite materials to provide magnetic losses and construct three-dimensional conductive networks are key strategies to alleviate the impedance mismatch between materials and free space. This can allow more electromagnetic waves to enter the interior of the composite material and enhance multiple reflections and scattering within the material.

[0004] High-performance EMW absorbers are inseparable from the selection of excellent absorbing materials. Two-dimensional (2D) materials, such as graphene (GO), MoS2, layered double hydroxides (LDHs), MXenes, etc., have attracted widespread attention due to their unique atomic layer thickness, high specific surface area, and excellent processing performance. However, a single two-dimensional material will cause severe impedance mismatch and cause secondary radiation of electromagnetic waves.

[0005] CoFe2O4 is widely used in the field of wave absorption because of its low price, simple preparation method and magnetic properties. However, CoFe2O4 has problems such as single loss mode, high density and easy aggregation of particles, which makes it difficult to meet the requirements of new wave absorbing materials. In order to improve the problem of high density of CoFe2O4, the preparation process can be changed to synthesize materials with hollow structures, which can reduce the density of the material on the one hand and make the impedance matching characteristics of the material with air better on the other hand.

[0006] In recent years, biomass materials used for shielding have attracted widespread attention due to their low cost and renewability. Gelatin is a non-crystalline natural polymer obtained by hydrolyzing collagen in animal skin, bones, etc. It is mainly composed of protein macromolecular chains connected by amino and carboxyl groups. It has the characteristics of high density and easily functionalized functional surface groups. Hydroxyethyl cellulose has abundant hydroxyl groups on its surface, which can easily form hydrogen bonds with the molecular chains of polymers such as gelatin. Polymer aerogels usually have stable physical properties, maintain low density and high porosity, good toughness, and are easy to process and shape. The existing technology lacks an absorbing material that combines the excellent properties of graphene, CoFe2O4 and gelatin / hydroxyethyl cellulose aerogel.

[0007] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0008] The present invention provides a porous core-shell absorbing aerogel and a preparation method thereof, aiming to solve the technical problems mentioned in the above background technology section existing in the prior art.

[0009] Content of the present invention is as follows:

[0010] The first aspect of the present invention provides a method for preparing a porous core-shell absorbing aerogel, comprising:

[0011] Providing or preparing gelatin / hydroxyethyl cellulose aerogel;

[0012] Providing or preparing a dispersion of a hollow CoFe2O4@graphene composite material;

[0013] immersing the gelatin / hydroxyethyl cellulose aerogel in the dispersion;

[0014] The gelatin / hydroxyethyl cellulose aerogel is taken out from the dispersion and dried to obtain a porous core-shell absorbing aerogel.

[0015] In an optional embodiment of the first aspect of the present invention, the preparation of gelatin / hydroxyethyl cellulose aerogel comprises:

[0016] Add gelatin and hydroxyethyl cellulose into distilled water and heat in a water bath to obtain a gelatin / hydroxyethyl cellulose solution;

[0017] adding glutaraldehyde solution as a cross-linking agent into the gelatin / hydroxyethyl cellulose solution and stirring evenly to obtain a cross-linked mixed solution;

[0018] The cross-linked mixed solution is pre-frozen and then freeze-dried to obtain gelatin / hydroxyethyl cellulose aerogel.

[0019] In an optional embodiment of the first aspect of the present invention, the mass ratio of gelatin to hydroxyethyl cellulose is (1-3):1, and the ratio of hydroxyethyl cellulose to distilled water is 1g:(40-60)mL; the temperature of water bath heating is 70-100°C; the pre-freezing temperature is 2-5°C, and the pre-freezing time is 2-4h; the freeze-drying temperature is -50--20°C, and the freeze-drying time is 30-50h.

[0020] In an optional embodiment of the first aspect of the present invention, the dispersion liquid for preparing the hollow CoFe2O4@graphene composite material comprises:

[0021] Evenly mixing ferric chloride hydrate, cobalt chloride hydrate and ethylene glycol to obtain a first solution;

[0022] Adding polyethylene glycol, polyvinyl pyrrolidone and urea to the first solution and mixing them evenly to obtain a second solution;

[0023] The second solution is heated to a first temperature and then kept warm for a first time, and then the first reaction product is collected from the second solution by magnetic force and washed and dried to obtain hollow CoFe2O4 powder;

[0024] The hollow CoFe2O4 powder is added into a cationic polyelectrolyte-polydiallyldimethylammonium chloride solution and stirred evenly, and the second reaction product is collected and washed and dried to obtain a PDDA-CoFe2O4 composite material;

[0025] The PDDA-CoFe2O4 composite material is added to the pre-prepared graphene solution, and after sufficient stirring, a dispersion of the hollow CoFe2O4@graphene composite material is obtained.

[0026] In an optional embodiment of the first aspect of the present invention, the molar mass ratio of hydrated ferric chloride and hydrated cobaltous chloride is (2-3):1; the ratio of hydrated ferric chloride and ethylene glycol is 1 mmol:(10-30) mL; the volume ratio of ethylene glycol and polyethylene glycol is (10-30):1; the mass ratio of polyvinyl pyrrolidone and urea is (1-2):1; the first temperature is 150-300°C, and the first time is 6-10 hours.

[0027] In an optional embodiment of the first aspect of the present invention, the first reaction product is washed by alternating washing with deionized water and anhydrous ethanol; the first reaction product is dried by vacuum drying at 60-100°C for 2-5 hours; the second reaction product is washed by anhydrous ethanol, and the second reaction product is dried by vacuum drying at 60-100°C for 1-3 hours; the mass ratio of the PDDA-CoFe2O4 composite material to the graphene in the graphene solution is (2-4):1.

[0028] In an optional embodiment of the first aspect of the present invention, immersing the gelatin / hydroxyethyl cellulose aerogel in the dispersion includes: immersing the gelatin / hydroxyethyl cellulose aerogel in the dispersion for a second time.

[0029] In an optional embodiment of the first aspect of the present invention, the mass of the solute in the dispersion is 20 to 40 mg / mL; the second time is 2 to 5 h.

[0030] In an optional embodiment of the first aspect of the present invention, the step of removing the gelatin / hydroxyethyl cellulose aerogel from the dispersion and drying it to obtain a porous core-shell absorbing aerogel comprises:

[0031] The gelatin / hydroxyethyl cellulose aerogel is taken out from the dispersion and dried at 70-100° C. to obtain a porous core-shell absorbing aerogel.

[0032] The second aspect of the present invention provides a porous core-shell absorbing aerogel, which is prepared by the preparation method of the porous core-shell absorbing aerogel according to any one of the first aspects above.

[0033] Beneficial effects: The present invention provides a porous core-shell absorbing aerogel and a preparation method thereof. The preparation method of the porous core-shell absorbing aerogel comprises providing or preparing gelatin / hydroxyethyl cellulose aerogel; providing or preparing a dispersion of a hollow CoFe2O4@graphene composite material; immersing the gelatin / hydroxyethyl cellulose aerogel in the dispersion; taking out the gelatin / hydroxyethyl cellulose aerogel from the dispersion and drying it to obtain a porous core-shell absorbing aerogel. The present invention is based on gelatin / hydroxyethyl cellulose aerogel and uses a hollow CoFe2O4@graphene composite material as an electromagnetic wave absorber to prepare a porous core-shell absorbing aerogel by an impregnation method. The porous structure of the aerogel and the hollow CoFe2O4@graphene composite material can effectively improve the impedance mismatch phenomenon and reduce the reflection of electromagnetic waves, and CoFe2O4 has magnetism to cause magnetic loss of electromagnetic waves. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The present invention is a flow chart of a method for preparing a porous core-shell absorbing aerogel. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0036] See also Figure 1 The first aspect of the present invention provides a method for preparing a porous core-shell absorbing aerogel. In general, the present invention uses biomass materials as raw materials to prepare porous aerogels by freeze-drying, impregnates hollow CoFe2O4@GO (graphene) composite materials, and introduces a variety of electromagnetic wave loss mechanisms to achieve the purpose of efficiently absorbing electromagnetic waves. The preparation method comprises the following steps:

[0037] S100, providing or preparing gelatin / hydroxyethyl cellulose aerogel; in an optional embodiment of step S100 of the present invention, the preparation of gelatin / hydroxyethyl cellulose aerogel comprises:

[0038] Gelatin and hydroxyethyl cellulose are added to distilled water and heated in a water bath to obtain a gelatin / hydroxyethyl cellulose solution; the mass ratio of gelatin to hydroxyethyl cellulose is (1-3):1, for example, 1:1, 2:1 and 3:1, and the ratio of hydroxyethyl cellulose to distilled water is 1g:(40-60)mL, for example, 1g:40mL, 1g:50mL and 1g:60mL; the temperature of the water bath heating is 70-100°C, for example, 70°C, 90°C and 100°C; glutaraldehyde solution is added as a cross-linking agent to the gelatin / hydroxyethyl cellulose solution and stirred evenly to obtain a cross-linked mixed solution; the cross-linked mixed solution is pre-frozen and then freeze-dried to obtain a gelatin / hydroxyethyl cellulose aerogel. The pre-freezing temperature is 2 to 5°C, for example, 2°C, 4°C and 5°C, and the pre-freezing time is 2 to 4h, for example, 2h, 3h and 4h; the freeze-drying temperature is -50 to -20°C, for example, -50°C, -40°C and -20°C, and the freeze-drying time is 30 to 50h, for example, 30h, 40h and 50h.

[0039] S200, providing or preparing a dispersion of a hollow CoFe2O4@graphene composite material; in an optional embodiment of step S200 of the present invention, the preparation of the dispersion of the hollow CoFe2O4@graphene composite material comprises:

[0040] Mix hydrated ferric chloride, hydrated cobalt chloride and ethylene glycol to obtain a first solution; the molar mass ratio of hydrated ferric chloride and hydrated cobalt chloride is (2-3):1, for example, 2:1 and 3:1; the ratio of hydrated ferric chloride and ethylene glycol is 1 mmol:(10-30) mL, for example, 1 mmol:10 mL, 1 mmol:20 mL and 1 mmol:30 mL; the volume ratio of ethylene glycol and polyethylene glycol is (10-30):1, 10:1, 20:1 and 30:1; the mass ratio of polyvinyl pyrrolidone and urea is (1-2):1, for example, 1:1 and 2:1; add polyethylene glycol, polyvinyl pyrrolidone and urea to the first solution and mix them to obtain a second solution;

[0041] The second solution is heated to a first temperature and then kept warm for a first time, and then the first reaction product is collected from the second solution by magnetic force and washed and dried to obtain hollow CoFe2O4 powder; the first temperature is 150-300°C, for example, 150°C, 200°C and 300°C, and the first time is 6-10h, for example, 6h, 8h and 10h; the first reaction product is washed by alternating washing with deionized water and anhydrous ethanol; the first reaction product is dried by vacuum drying at 60-100°C (for example, 60°C, 80°C and 100°C) for 2-5h (for example, 2h, 4h and 5h);

[0042] The hollow CoFe2O4 powder is added into a cationic polyelectrolyte-polydiallyldimethylammonium chloride solution and stirred evenly, and the second reaction product is collected and washed and dried to obtain a PDDA-CoFe2O4 composite material; the second reaction product is washed by anhydrous ethanol, and the second reaction product is dried by vacuum drying at 60 to 100° C. (for example, 60° C., 80° C. and 100° C.) for 1 to 3 h (for example, 1 h, 2 h and 3 h);

[0043] The PDDA-CoFe2O4 composite material is added to a pre-prepared graphene solution, and after sufficient stirring, a dispersion of a hollow CoFe2O4@graphene composite material is obtained. The mass ratio of the PDDA-CoFe2O4 composite material to the graphene in the graphene solution is (2-4):1, for example, 2:1, 3:1 and 4:1.

[0044] S300, immersing the gelatin / hydroxyethyl cellulose aerogel in the dispersion; in an optional embodiment of step S300, immersing the gelatin / hydroxyethyl cellulose aerogel in the dispersion includes: immersing the gelatin / hydroxyethyl cellulose aerogel in the dispersion for a second time; the mass of the solute in the dispersion is 20 to 40 mg / mL, for example, 20 mg / mL, 30 mg / mL and 40 mg / mL; the second time is 2 to 5 h, for example, 2 h, 3 h and 5 h.

[0045] S400, taking out the gelatin / hydroxyethyl cellulose aerogel from the dispersion and drying it to obtain a porous core-shell absorbing aerogel. In an optional embodiment of step S300 of the present invention, taking out the gelatin / hydroxyethyl cellulose aerogel from the dispersion and drying it to obtain a porous core-shell absorbing aerogel comprises: taking out the gelatin / hydroxyethyl cellulose aerogel from the dispersion and drying it at 70 to 100°C (e.g., 70°C, 90°C, and 100°C) to obtain a porous core-shell absorbing aerogel.

[0046] The second aspect of the present invention provides a porous core-shell absorbing aerogel, which is prepared by the method for preparing the porous core-shell absorbing aerogel described in any one of the first aspects. The porous core-shell absorbing aerogel of the present invention first adopts a freeze-drying method to prepare a biomass porous aerogel, and uses a hollow CoFe2O4@GO composite material as an electromagnetic wave absorber to prepare the porous core-shell absorbing aerogel by an impregnation method, wherein the porous structure of the aerogel and the hollow CoFe2O4@GO composite material can effectively improve the impedance mismatch phenomenon and reduce the reflection of electromagnetic waves, and CoFe2O4 has magnetism to absorb electromagnetic waves by magnetic loss.

[0047] In order to better illustrate the effect of the technical solution of the present invention, the present invention constructed the following embodiments and carried out relevant performance tests, and the results are as follows:

[0048] Embodiment 1:

[0049] (1) Preparation of gelatin / hydroxyethyl cellulose aerogel: 2 g of gelatin and 1 g of hydroxyethyl cellulose were added to 50 mL of distilled water, heated and stirred in a water bath at 80°C until completely dissolved to obtain a gelatin / hydroxyethyl cellulose solution, and then 1 mL of a 15 wt% glutaraldehyde solution was added as a cross-linking agent, stirred for 5 min, and pre-frozen in a 4°C refrigerator for 3 h. Freeze-dried at -40°C for 48 h to obtain a gelatin / hydroxyethyl cellulose aerogel;

[0050] (2) Preparation of hollow CoFe2O4@GO composite material: First, 5mmol of FeCl3·6H2O, 2.5mmol of CoCl2·6H2O, and 40.0mL of ethylene glycol were stirred evenly at room temperature. Then 2.0mL of polyethylene glycol (PEG-400), 4.0g of polyvinyl pyrrolidone (PVP-K30), and 3.6g of urea were added and mixed evenly. The mixture was heated to 200℃, kept warm for 8h, collected by magnetic attraction, and washed alternately with deionized water and anhydrous ethanol, and finally dried under vacuum at 80℃ for 3h to obtain hollow CoFe2O4. The obtained CoFe2O4 powder was added into 50mL of cationic polyelectrolyte-polydiallyldimethylammonium chloride (PDDA, 0.5%) solution, stirred vigorously for 2h at room temperature, washed with anhydrous ethanol three times, and dried under vacuum at 80℃ for 2h to obtain PDDA-CoFe2O4 composite material. According to the mass ratio of PDDA-CoFe2O4:GO of 3:1, the PDDA-CoFe2O4 solution was added dropwise into the pre-prepared GO solution (5mg / mL) and stirred for 5h to obtain the core-shell hollow CoFe2O4@GO dispersion.

[0051] (3) Preparation of porous core-shell absorbing aerogel: The gelatin / hydroxyethyl cellulose aerogel prepared in step (1) was immersed in 20 mg / mL CoFe2O4@GO dispersion for 2 h and dried at 80°C to obtain a porous core-shell absorbing aerogel.

[0052] Embodiment 2:

[0053] (1) The preparation of gelatin / hydroxyethyl cellulose aerogel is consistent with Example 1 (1).

[0054] (2) Preparation of hollow CoFe2O4@GO composite material: First, 4mmol of FeCl3·6H2O, 1.5mmol of CoCl2·6H2O, and 30.0mL of ethylene glycol were stirred evenly at room temperature. Then 1.0mL of polyethylene glycol (PEG-400), 3.0g of polyvinyl pyrrolidone (PVP-K30), and 2.6g of urea were added and mixed evenly. The mixture was heated to 200℃, kept warm for 8h, collected by magnetic attraction, and washed alternately with deionized water and anhydrous ethanol. Finally, it was dried under vacuum at 80℃ for 3h to obtain hollow CoFe2O4. The obtained CoFe2O4 powder was added into 50mL of cationic polyelectrolyte-polydiallyldimethylammonium chloride (PDDA, 0.5%) solution, stirred vigorously for 2h at room temperature, washed with anhydrous ethanol three times, and dried under vacuum at 80℃ for 2h to obtain PDDA-CoFe2O4 composite material. According to the mass ratio of PDDA-CoFe2O4:GO of 5:1, the PDDA-CoFe2O4 solution was added dropwise into the pre-prepared GO solution (5mg / mL) and stirred for 5h to obtain the core-shell hollow CoFe2O4@GO dispersion.

[0055] (3) Preparation of porous core-shell absorbing aerogel: The gelatin / hydroxyethyl cellulose aerogel prepared in step (1) was immersed in 30 mg / mL CoFe2O4@GO dispersion for 2 h and dried at 80°C to obtain a porous core-shell absorbing aerogel.

[0056] The porous core-shell absorbing aerogel of the present invention introduces a variety of electromagnetic wave loss mechanisms to achieve the purpose of efficient electromagnetic wave absorption. The aerogel thickness of Example 1 is only 3.32 mm, and the RLmin is -61.2 dB at 7.58 GHz, and the effective absorption band is as high as 5.15 GHz. The aerogel thickness of Example 2 is 3.84 mm, and the RLmin is -65.8 dB at 8.48 GHz, and the effective absorption band is as high as 5.26 GHz.

[0057] In summary, the present invention provides a porous core-shell absorbing aerogel and a preparation method thereof. The preparation method of the porous core-shell absorbing aerogel includes providing or preparing a gelatin / hydroxyethyl cellulose aerogel; providing or preparing a dispersion of a hollow CoFe2O4@graphene composite material; immersing the gelatin / hydroxyethyl cellulose aerogel in the dispersion; taking out the gelatin / hydroxyethyl cellulose aerogel from the dispersion and drying it to obtain a porous core-shell absorbing aerogel. The present invention is based on gelatin / hydroxyethyl cellulose aerogel and uses a hollow CoFe2O4@graphene composite material as an electromagnetic wave absorber to prepare a porous core-shell absorbing aerogel by an impregnation method. The porous structure of the aerogel and the hollow CoFe2O4@graphene composite material can effectively improve the impedance mismatch phenomenon and reduce the reflection of electromagnetic waves, and CoFe2O4 has magnetism to cause magnetic loss of electromagnetic waves.

[0058] As described above, the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a porous core-shell absorbing aerogel, It is characterized in that include: Providing or preparing gelatin / hydroxyethyl cellulose aerogel; Providing or preparing hollow CoFe 2 O 4 @Dispersion of graphene composite materials; immersing the gelatin / hydroxyethyl cellulose aerogel in the dispersion; The gelatin / hydroxyethyl cellulose aerogel is taken out from the dispersion and dried to obtain a porous core-shell absorbing aerogel.

2. The method for preparing the porous core-shell absorbing aerogel according to claim 1, It is characterized in that The preparation of gelatin / hydroxyethyl cellulose aerogel comprises: Add gelatin and hydroxyethyl cellulose into distilled water and heat in a water bath to obtain a gelatin / hydroxyethyl cellulose solution; adding glutaraldehyde solution as a cross-linking agent into the gelatin / hydroxyethyl cellulose solution and stirring evenly to obtain a cross-linked mixed solution; The cross-linked mixed solution is pre-frozen and then freeze-dried to obtain gelatin / hydroxyethyl cellulose aerogel.

3. The method for preparing the porous core-shell absorbing aerogel according to claim 2, It is characterized in that The mass ratio of gelatin to hydroxyethyl cellulose is (1-3):1, and the ratio of hydroxyethyl cellulose to distilled water is 1 g:(40-60) mL; the temperature of water bath heating is 70-100° C.; the pre-freezing temperature is 2-5° C., and the pre-freezing time is 2-4 h; the freeze-drying temperature is -50--20° C., and the freeze-drying time is 30-50 h.

4. The method for preparing the porous core-shell absorbing aerogel according to claim 2, It is characterized in that The preparation of hollow CoFe 2 O 4 @The dispersion of graphene composite materials includes: Evenly mixing ferric chloride hydrate, cobalt chloride hydrate and ethylene glycol to obtain a first solution; Adding polyethylene glycol, polyvinyl pyrrolidone and urea to the first solution and mixing them evenly to obtain a second solution; The second solution is heated to a first temperature and then kept warm for a first time, and then the first reaction product is collected from the second solution by magnetic force and washed and dried to obtain a hollow CoFe 2 O 4 powder; The hollow CoFe 2 O 4 The powder was added into the cationic polyelectrolyte-polydiallyldimethylammonium chloride solution and stirred evenly. The second reaction product was collected and washed and dried to obtain PDDA-CoFe 2 O 4 Composite materials; The PDDA-CoFe 2 O 4 The composite material is added to the pre-prepared graphene solution and stirred thoroughly to obtain the hollow CoFe 2 O 4 @Dispersion of graphene composite material.

5. The method for preparing the porous core-shell absorbing aerogel according to claim 4, It is characterized in that The molar mass ratio of hydrated ferric chloride to hydrated cobaltous chloride is (2-3):1; the ratio of hydrated ferric chloride to ethylene glycol is 1 mmol:(10-30) mL; the volume ratio of ethylene glycol to polyethylene glycol is (10-30):1; the mass ratio of polyvinyl pyrrolidone to urea is (1-2):1; the first temperature is 150-300° C., and the first time is 6-10 hours.

6. The method for preparing the porous core-shell absorbing aerogel according to claim 4, It is characterized in that The first reaction product is washed with deionized water and anhydrous ethanol alternately; the first reaction product is dried at 60-100° C. in vacuum for 2-5 h; the second reaction product is washed with anhydrous ethanol and the second reaction product is dried at 60-100° C. in vacuum for 1-3 h; the PDDA-CoFe 2 O 4 The mass ratio of the composite material to the graphene in the graphene solution is (2-4):

1.

7. The method for preparing the porous core-shell absorbing aerogel according to claim 2, It is characterized in that The immersing the gelatin / hydroxyethyl cellulose aerogel in the dispersion includes: immersing the gelatin / hydroxyethyl cellulose aerogel in the dispersion for a second time.

8. The method for preparing the porous core-shell absorbing aerogel according to claim 7, It is characterized in that The mass of the solute in the dispersion is 20 to 40 mg / mL; and the second time is 2 to 5 hours.

9. The method for preparing the porous core-shell absorbing aerogel according to claim 1, It is characterized in that The step of taking out the gelatin / hydroxyethyl cellulose aerogel from the dispersion and drying it to obtain a porous core-shell absorbing aerogel comprises: The gelatin / hydroxyethyl cellulose aerogel is taken out from the dispersion and dried at 70-100° C. to obtain a porous core-shell absorbing aerogel.

10. A porous core-shell absorbing aerogel, It is characterized in that The porous core-shell absorbing aerogel is prepared by the preparation method of any one of claims 1 to 9.

Citation Information

Cited By

  • Aerogel modified based on polyphenol modified HA nanorod, and preparation method and application thereof

    CN121181282A